Electrospun Polymer-Inorganic Nanostructured Materials and Their Applications. (2nd July 2020) - Homocianu, Mihaela; Pascariu, Petronela
Abstract: Materials based on polymer-inorganic nanostructures, e(Polym/INS), produced by combining functional polymers with inorganic nanostructured compounds represent a major area of research with many applications. This review provides a summary of the most relevant polymer-inorganic nanostructured systems found in the literature over the last decade. Then the most relevant and specific features of these systems are described. Finally, we summarize the progress made over the last decade in the development of polymer-inorganic electrospun hybrid materials with various morphologies, compositions and applications in environmental remediation, sensors, catalysts, energy area and biomedical uses.